Articulations of Locality: Portraits and Narratives from the Toronto-Cuban Musicscape - Gallaugher, Annemarie (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1999)
In keeping with a current movement in ethnomusicology and popular music studies concerned with musical constructions of space, time, and other, this paper presents a mini-ethnography of the Toronto-Cuban musicscape. Using as a point of departure Sara Cohen's statement that "We are all multiply placed with multiple identities but that does not necessarily mean that we are well-placed" (1995), the paper highlights some of the problems and discrepancies—i.e., the more negative, troublesome, and less coherent sides of placement—involved in the multiple and heterogeneous articulations of Cuban-ness within this locality.